Premalignant lesions of the cervix. - Castellano, Carlos (2015)
Dysplasia, carcinoma in situ and cervical carcinoma microinvasive are taking great importance in the problem of cervical cancer. Undoubtedly, the increasing frequency with which these diagnoses are made is directly related to the wider dissemination of colpocytology Pap. Obviously, where more centers use this diagnostic method will most cases diagnosed incipient dysplasias and malignant lesions and a significant decrease in advanced cases. The current doctor should know the importance of cytological screening and how to do it, as also the significance of cytologic reports in order to identify patients requiring further research. Finally, he must learn what it is investigating a suspected case and carry it out if you are qualified or refer to another who is trained in this field.